PENGARUH PENDAPATAN ASLI DAERAH TERHADAP BELANJA DAERAH DI KOTA LHOKSEUMAWE - Irdawati Irdawati; Ratna Ratna; Maisyuri Maisyuri (Jurnal Akuntansi dan Pembangunan (JAKTABANGUN) STIE Lhokseumawe, 2017)
This research aims to find out the influence of local revenues to local expenses. The data used in this research was taken from Local Financial Services and Local Asset (DPKAD) from the year of 2005 until 2014. The method used in this research is simple linear regression method. The result of this research is local revenues significantly influenced to local expenses and positively. Suggestion for next research is that to use complete data and use more variable, in order to get satisfied result.